Cryogenics - Zobiri,Oussama (University of Eloued جامعة الوادي, 2025)
Cryogenics is the scientific module that focuses on the production, study, and application of extremely low temperatures, typically below –150°C. At such temperatures, the physical behavior of materials changes dramatically, allowing scientists and engineers to explore unique properties of gases, liquids, and solid materials. One of the most important outcomes of cryogenics is the liquefaction of gases such as nitrogen, oxygen, and helium, which enables their storage and use in compact and stable forms. Cryogenic systems rely on specialized equipment including cryocoolers, liquefiers, insulated, and vacuum-jacketed piping designed to minimize heat transfer. These systems allow precise temperature control and are essential in many scientific and industrial applications. In medicine, cryogenics enables the operation of machines through superconducting magnets cooled with liquid helium. It is also used in cryosurgery, cryopreservation of biological samples, and long-term storage of genetic materials. In space and aviation, cryogenic fuels such as liquid hydrogen play a crucial role in high-efficiency propulsion. Cryogenics is also vital in particle physics, where accelerators require ultra-low temperatures to maintain superconductivity. Despite its benefits, the field faces challenges such as material brittleness, safety risks, and the need for advanced insulation. Overall, cryogenics remains a key technology enabling innovation in research, medicine, and aerospace
Pedagogical publication aimed at second-year Master's students in Energy
Keywords: : Gas Liquefaction Cycle; Joule–Thomson Effect; Turbo-expander; Phase Transition; Critical Temperature